Computer Mouse Usage Among Computer Gamers And Its Association With Trigger Finger And Carpal Tunnel Syndrome - Apendai, Luqman; Adnan, Ammar; Radin Umar, Radin Zaid; Samuel, Siby; Hamid, Malek (Human Factors And Ergonomics Society Malaysia (HFEM), 2017)
Computer mouse design has evolved throughout generation. Most people are using computer mouse to do work and for entertainment. However, due to repetitive actions involving hand, it could lead to Trigger Finger and Carpal Tunnel syndromes. Objectives of the study are: (i) to evaluate the relationship between computer mouse’s usage during playing online games – number of keystroke, number of buttons clicking, distance of computer mouse dragging, and duration of active on game – and Trigger Finger syndrome via Trigger Finger test; and (ii) to evaluate the relationship between computer mouse’s usage during playing online games – number of keystroke, number of buttons clicking, distance of computer mouse dragging, and duration of active on game – and Carpal Tunnel syndrome via Phalen’s test. Thirty participants are recruited for the study. A participant are asked to download a software called ‘Mousotron’ on his computer system that provide data of his or her pattern of computer mouse usage - number of keystroke, number of buttons clicking, distance of computer mouse dragging, and duration of active on game. After that, participants are required to come to the laboratory for the assessment phase in which the Trigger Finger and Phalen’s tests are assessed. The interactions between the variables are analyzed and the results show a positive correlation for all interactions. The findings show how spending time playing video games will affect one’s health – specifically the hands.